Subject grammar forms in the semantic-syntactic structure of a sentence - Riznyk, Serhii (Ukrainian Linguistics, 2022)
The article is devoted to the analysis of case forms that implement the subjective meaning in the semantic structure of a simple sentence. The attention is paid to the noun forms of the nominative, vocative, genitive, dative, accusative and instrumental cases of an agent in the Ukrainian sentence. The grammar functions of an agent in different cases are considered, i.e. of a subject in the nominative and vocative cases, of an object in the genitive, dative, accusative and instrumental cases. Background. The analysis of the sentence semantics involves the study of the interaction between its semantic and formal layout. The interrelation between sentence semantic and syntactic structures reveals formal models of predicative grammar constructions. Purpose. The analysed models with subject syntaxemes denoting an agent, an experiencer, an actor, quantity, quality, and a location enable linguists and language learners to determine the grammatical means of expressing substantive (subject) semantics. Methods. In the study of grammatical forms of subject syntaxemes, the structural method is used, in particular, the methods of sentence model transformation and component analysis. In a number of cases, these techniques helped to reveal that a substantive syntaxeme with subject semantics, expressed in the indirect (genitive, dative, accusative, instrumental) case, is regularly transformed into a subject syntaxeme in the nominative case in the grammatical position of the subject. Results. The grammar models considered in the article demonstrate that the semantic subject of the Ukrainian sentence can be expressed by all case forms without preposition. The variety of forms and means of subject expression allows the noun and its equivalents to realize their agent function in a semantic-syntactic combination with predicates of both verbal and its derivative forms (noun, numeral, adjective, adverbial) nature. Conclusion. The main grammar form of expressing subjectivity is the nominative case combined with a predicate of action, state, process, quantitative, qualitative or locative feature. The vocative case regularly denotes the subject of addressed speech, the other morphological forms of subjects (genitive, dative, accusative, instrumental) have a much narrower application in the Ukrainian sentence.